Inactivation of poliovirus in digested sludge - Robyn L. Ward; C.S. Ashley (1976)
The effect of anaerobically digested sludge on poliovirus during incubation at temperatures between 28 and 4 C was studied. Although virus was fully recoverable from sludge, its infectivity decreased in proportion to the time and temperature of incubation. The rate ranged from greater than 1 log per day at 28 C to about 1 log every 5 days at 4 C. The mechanism of inactivation was studied at the lower temperature where the sedimentation coefficients of most inactivated particles were not detectably modified. The ribonucleic acid (RNA) of these particles appeared to have been nicked and had an average sedimentation value about 70% that of RNA from infectious virus. Since the specific infectivity of RNA from particles recovered from sludge was directly proportional to that of the particles from which it was extracted, loss of infectivity was probably due to inactivation of RNA. Some breakdown was also found in the two largest viral proteins of inactivated particles. Thus, the mechanism of inactivation may be cleavage of viral proteins followed by nicking of encapsulated RNA. Because no virucidal activity was found in raw sludge, this component of digested sludge appears to be a product of the digestion process.